Becoming a disagreeable citizen – disagreement orientation and citizenship education: A multilevel analysis of Norwegian adolescents’ disagreement orientation - Dahl, Kjersti (JSSE - Journal of Social Science Education, 2024)
Highlights: The findings support viewing disagreement orientation as multidimensional, with debate seeking and conflict aversion being twodistinct dimensions of disagreement orientation There are different factors that impact debate seeking and conflict Characteristics of citizenship education has impact on conflict avoidance, but not debate seeking. Debate seeking is related to individual background variables, such as political interest, political conversation, and news-consumption Purpose: This study explores debate seeking and conflict avoidance as dimensions of disagreement orientation, and how factors such as citizenship education and individual background may impact how young people engage in situations with conflicting political perspectives. The aim is to study whether how we facilitate citizenship education may affect young people to be more comfortable with political disagreement. Design/methodology/approach: Multilevel modelling and factor analysis is performed using a survey among a selection of Norwegian fifteen-year-olds. Findings: Citizenship education characteristics impact conflict avoidance but not debate seeking. Debate seeking is rather related to individual background factors such as political interest and attention paid to the news. Finally, the dimensions form basis of a potential typology of young people’s disagreement orientation Research limitations/implications: Further research is needed to establish causality, however the results have implications for the role of disagreement in teacher education and classrooms.